Symbiotic Microbes from Marine Invertebrates: Driving a New Era of Natural Product Drug Discovery - Alix Blockley; David R. Elliott; Adam P. Roberts; Michael Sweet (Diversity, 2017)
Invertebrates account for more than 89% of all extant organisms in the marine environment, represented by over 174,600 species (recorded to date). Such diversity is mirrored in (or more likely increased by) the microbial symbionts associated with this group and in the marine natural products (or MNPs) that they produce. Since the early 1950s over 20,000 MNPs have been discovered, including compounds produced by symbiotic bacteria, and the chemical diversity of compounds produced from marine sources has led to them being referred to as "blue gold" in the search for new drugs. For example, 80% of novel antibiotics stemming from the marine environment have come from Actinomycetes, many of which can be found associated with marine sponges, and compounds with anti-tumorigenic and anti-diabetic potential have also been isolated from marine symbionts. In fact, it has been estimated that marine sources formed the basis of over 50% of FDA-approved drugs between 1981 and 2002. In this review, we explore the diversity of marine microbial symbionts by examining their use as the producers of novel pharmaceutical actives, together with a discussion of the opportunities and constraints offered by “blue gold” drug discovery.